Role of oxygen vacancies in water gas shift reaction: activity study on BaCe0.98-xYxPt0.02O3-delta perovskites - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Physical Chemistry C, 2014)
Oxygen vacancies are suggested to play an important role in reactions like water gas shift where the redox mechanism is crucial. Pt-doped BaCeO3 perovskite, moderately active for water gas shift reaction, is selected for further understanding the role of oxygen vacancies, since perovskite lattice can tolerate and stabilize vacancies facilitating an accurate quantification. Vacancies are created in the system by systematic doping of increasing amounts of Y. Structure and activity studies reveal that the 6% Y-substituted compound which has the most symmetric B site coordination environment exhibits the highest activity. Hence, it is not the extent of vacancies but their structural characteristics which are found to be decisive. Symmetric coordination around B ions facilitates water adsorption and dissociation by lowering the energy barriers due to the creation of an isotropic environment.